Indukanta ghritam - An ayurvedic formulation for acid peptic disorder and longevity: A review - Punam Aggarwal; R Galib; P K Prajapati; Pramod R Yadav (Wolters Kluwer Medknow Publications, 2021)
Introduction: Acid peptic disorders are common conditions reported in daily clinical practice in India. Epidemiological study of 30,216 patients inferred 7.8% prevalence of peptic ulcer in India, while prevalence of gastroesophageal reflux is reported to be around 28% in South West India. Repeated gastric ulcers, perforation, or hemorrhage can cause intestinal fibrosis or cancer which can lead to death. As the disease occurs mostly in Madhyama vayas (16-70 yrs of age) and if this age is affected, longevity also be affected. Based on the clinical features, such manifestations can be compared with Amlapitta and Parinama shula. These diseases are preventable and, if not addressed at the right time, may burden the scenario hampering the quality of life of the individuals. Objective: To screen the activities of individual ingredients of Indukanta ghritam and to propose possible mode of action in APDs and longevity. Data Source: Charaka Samhita, Sushruta Samhita, Ashtanga Hridaya, Sahasra yoga, Sharangadhara Samhita and online data bases. Review Methods: The classical text books were reviewed manually and review was also done by referring various scientific journals and other databases. Results: The formulation is a combination of several drugs, i.e., Dashamoola and Panchakola etc. They are referred to be useful in Amlapitta, Parinama shula etc. conditions and latest researches have established activities like gastroprotective, antioxidant, immuno-modulation etc. inferring the use of the formulation the therapeutics of APDs, as well as a rejuvenating drug. Conclusion: Indukanta ghritam can prevent as well as cure the disease and can improve the quality of life. The herbal formulation can minimize the disease burden and possibly can play an important role as a classical rejuvenating drug.